Assessment of Nurses' Knowledge about Early Clinical Manifestation of Herpes Zoster - Harith Fathi Khudhayer Al-Aubaid; Ali Mohammed Fathi; Nasir Muwfaq Younis (Public Health of Indonesia, 2026)
Background: VZV stays dormant in the dorsal root spinal ganglia after chickenpox resolves, and it can reactivate at any time, though it usually does so later in life to cause herpes zoster. Objective: The purpose of this study is to evaluate nurses' understanding of the early clinical signs of herpes zoster. Methods: The study was descriptive in nature. From November 4, 2024, to April 1, 2025, nurses' knowledge of early clinical signs of herpes zoster was assessed using a purposive (non-probability) sample drawn from four teaching hospitals in the Nineveh Governorate. There were two sections to the study:  Age, gender, degree, and years of experience were among the demographic data collected in the first section of the study. Six key questions concerning nurses' awareness of the early clinical signs of herpes zoster were asked in the second section. The Statistical Package for the Social Sciences (SPSS) version 27 was used to analyze the data. Results: In the study, 23 nurses (76.7%) received a low level, while 7 nurses (23.3%) received a high level, out of all the nurses who completed the questionnaire. While the relationship between demographic characteristics and nurses' knowledge of the clinical signs of herpes zoster was very weak. Conclusions: According to the study's findings, nurses' understanding of general information, symptoms, and signs was significant, but their understanding of nursing care and treatment was non-significant. The socio-demographic factors and nurses' knowledge had a weak correlation.